2019
DOI: 10.3390/microorganisms8010018
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes in Export-approved Beef from Mato Grosso, Brazil: Prevalence, Molecular Characterization and Resistance to Antibiotics and Disinfectants

Abstract: The Brazilian state of Mato Grosso is the largest producer and exporter of beef in the country, but few studies of relevance have been conducted to evaluate the microbiological safety of its products. This study aimed to estimate the prevalence of Listeria monocytogenes (LM) in export-approved beef from Mato Grosso and to characterize the isolates in terms of molecular properties and antimicrobial resistance. From a total of 50 samples analyzed, Listeria sp. was isolated in 18 (36% prevalence). Listeria monocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
2
19
1
Order By: Relevance
“…Similar to our results, Kuan et al [31] reported the L. monocytogenes prevalence of 33.3% in beef offal from different wet markets. In turn, from the total of 50 beef meat samples examined by Teixiera et al [4], six were confirmed as L. monocytogenes positive (12%). The differences reported in the L. monocytogenes prevalence in different meats are affected by various factors, e.g., control measures implementation during the stages of cleaning and disinfection [29].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Similar to our results, Kuan et al [31] reported the L. monocytogenes prevalence of 33.3% in beef offal from different wet markets. In turn, from the total of 50 beef meat samples examined by Teixiera et al [4], six were confirmed as L. monocytogenes positive (12%). The differences reported in the L. monocytogenes prevalence in different meats are affected by various factors, e.g., control measures implementation during the stages of cleaning and disinfection [29].…”
Section: Discussionmentioning
confidence: 95%
“…People particularly vulnerable to infection are the elderly, pregnant women, newborns, and immunocompromised individuals. In adult males and non-pregnant women listeriosis causes primary meningitis, encephalitis or septicaemia [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations